The influence a reading intervention programme for grade 8 learners in their first language (Afrikaans) has on their first and second language (English) reading skills - Stofberg, Elmarie (Stellenbosch : Stellenbosch University, 2011)
Thesis (MPhil )--Stellenbosch University, 2011.